Moral Property Rights in Bargaining - Simon Gaechter; Arno Riedl (Center for Economic Studies and ifo Institute (CESifo), 2002)
In many business transactions, in labor-management relations, in international conflicts, and welfare state reforms claims acquired in the past seem to create strong entitlements that shape current negotiations. Despite their importance, the role of entitlements in negotiations has not received much attention. We fill the gap by designing an experiment that allows us to measure the entitlements and to track them through the whole negotiation process. We find strong entitlement effects that shape opening offers, bargaining duration, concessions and reached (dis-)agreements. We argue that entitlements constitute a moral property right that is influential independent of negotiators' legal property rights.
Keywords: 330; moral property rights; fairness judgements; bargaining with claims; self-serving bias